PENDIDIKAN DAN BIMBINGAN BAGI ANAK CERDAS DAN BERBAKAT DI SEKOLAH DASAR UPTD SD NEGERI WELAI - Tersia Lengmalu; Vani E Maniyeni, Safri M Malaka, Yessy Mata, Petrus Mau Tellu Dony, Nehemia Fanpada, Halena Muna Bek (CV. Adiba Aisha Amira, 2025)
This study aims to determine guidance and counseling for intelligent and gifted children. The method used by the author is descriptive quantitative. For this reason, guidance and counseling services are needed to provide solutions so that obstacles do not occur to students or their friends. With the help of guidance and counseling services, students are given assistance through appropriate programs and techniques so that they can develop optimally according to their potential. Guidance and counseling at the elementary school level plays a role in helping achieve educational goals in elementary schools. These intelligent and academically gifted children are superior Indonesian human resources and are very low if ignored. Superior human resource assets must be considered because they have the right to education.